Acadian variant of Fanconi syndrome is caused by mitochondrial respiratory chain complex I deficiency due to a non-coding mutation in complex I assembly factor NDUFAF6 - Hartmannová, Hana; Piherová, Lenka; Tauchmannová, Kateřina; Kidd, Kendrah; Acott, Philip D; Crocker, John F S; Oussedik, Youcef; Mallet, Marcel; Hodaňová, Kateřina; Stránecký, Viktor; Přistoupilová, Anna; Barešová, Veronika; et al. (Human molecular genetics, 2016)
The Acadian variant of Fanconi Syndrome refers to a specific condition characterized by generalized proximal tubular dysfunction from birth, slowly progressive chronic kidney disease and pulmonary interstitial fibrosis. This condition occurs only in Acadians, a founder population in Nova Scotia, Canada. The genetic and molecular basis of this disease is unknown. We carried out whole exome and genome sequencing and found that nine affected individuals were homozygous for the ultra-rare non-coding variant chr8:96046914 T > C; rs575462405, whereas 13 healthy siblings were either heterozygotes or lacked the mutant allele. This variant is located in intron 2 of NDUFAF6 (NM_152416.3; c.298-768 T > C), 37 base pairs upstream from an alternative splicing variant in NDUFAF6 chr8:96046951 A > G; rs74395342 (c.298-731 A > G). NDUFAF6 encodes NADH:ubiquinone oxidoreductase complex assembly factor 6, also known as C8ORF38. We found that rs575462405-either alone or in combination with rs74395342-affects splicing and synthesis of NDUFAF6 isoforms. Affected kidney and lung showed specific loss of the mitochondria-located NDUFAF6 isoform and ultrastructural characteristics of mitochondrial dysfunction. Accordingly, affected tissues had defects in mitochondrial respiration and complex I biogenesis that were corrected with NDUFAF6 cDNA transfection. Our results demonstrate that the Acadian variant of Fanconi Syndrome results from mitochondrial respiratory chain complex I deficiency. This information may be used in the diagnosis and prevention of this disease in individuals and families of Acadian descent and broadens the spectrum of the clinical presentation of mitochondrial diseases, respiratory chain defects and defects of complex I specifically.
Keywords: respirační komplex I; Mitochondria; heterozygot; Male; Chromosome Mapping; homozygot; mutace; Genetic Predisposition to Disease; Heterozygote; genetická predispozice k nemoci; Mitochondrial Diseases; plíce; mitochondriální nemoci; Fanconi Syndrome; Kanada; Adult; Kidney; dospělí; mužské pohlaví; Homozygote; mitochondriální proteiny; Lung; Mitochondrial Proteins; exom; lidé; Fanconiho syndrom; ženské pohlaví; Exome; mapování chromozomů; Humans; ledviny; Electron Transport Complex I; Mutation; Alleles; Canada; Female; alely; lidé středního věku; mitochondrie; Middle Aged